Exploring the increasing behavior of thermal conductivity for high-entropy zirconates at high temperatures. (15th April 2023) - Zhang, Yonghe; Xie, Min; Wang, Zhigang; Song, Xiwen; Mu, Rende; Zhou, Fen; Bao, Jinxiao; Gao, Jianquan; Pan, Wei
Abstract: Up to present, the discussion on the increase of thermal conductivity at high temperatures for thermal barrier coatings is not comprehensive enough. The present study systematically explored the increased behavior of high temperature thermal conductivity for (La0.2 Gd0.2 Y0.2 Yb0.2 Er0.2 )2 (Zr1- x Ti x )2 O7 high-entropy ceramics. Above 600 ℃, the thermal conductivities of x = 0.1–0.5 components increase with composition and temperature. The significantly reduced emissivity and improved transmittance imply that the reason for the increase of high temperature thermal conductivity is the remarkable improvement of photon thermal conductivity. Importantly, this study provides a route to explore the different behavior of high temperature thermal conductivity by investigating phonon, photon and electronic heat conduction behaviors, which is also conducive to design and develop advanced thermal barrier coatings with low thermal conductivity. Graphical abstract: Image, graphical abstract